Complement activation in COVID-19 - Laurence, Jeffrey (Henry Stewart Talks, 2021)
The pathogenesis of COVID-19 mediated by complement activation, Indicators for complement activation in COVID-19, The interaction between coagulation and complement cascades, When to treat patients with anti-complement drugs